Anochetus maryatiae, a new species of ponerinae (hymenoptera: formicidae) - Nurul Aida .K.I; Idris .A.B (Universiti Kebangsaan Malaysia, 2011)
Anochetus maryatiae, a new species of Formicidae from the subfamily Ponerinae, tribe Ponerini from Ulu Gombak is described and illustrated. This ant genus was last studied in Malaysia by Brown in 1978. Observations were made on morphometric characters which included parameter measurements of total length, head length, head width, mandible length, scape length, antenna length, maximum eye length, oculomandibular distance, funicular length segment 1 to 4, pronotum width, propodeum height, petiole length, petiole height, dorsal petiole width, cephalix index and mandibular index. It was followed by a brief diagnosis, description of morphological structure, microsculpture, pilosity and discussion. Although it has resemblance with Anochetus tua, it could be easily distinguished from other species in having reticulate pronotum. This is the only species from Malaysia with such microsculpture on the pronotum. In addition to that, A. maryatie varies with A. tua in having smaller total length, less than 7.5 mm and lighter colour